Maternal Provisioning of Offspring With Defence Chemicals in a Facultatively Parthenogenetic Stick Insect - Ana Caroline Oliveira Vasconcelos; Lewis Adler; Russell Bonduriansky (Ecology and Evolution, 2025)
ABSTRACT Parents can invest in offspring by transferring environmental factors, such as nutrients or diet‐derived defence chemicals, into eggs or embryos. However, in systems where females can reproduce facultatively without a male (facultative parthenogenesis), it is not known how reproductive mode and maternal environment affect offspring provisioning. The facultatively parthenogenetic stick insect Megacrania batesii sprays a defensive fluid from paired prothoracic glands. Here, we report that some hatchlings of M. batesii can spray even prior to their first feeding and provide evidence that both eggs and hatchlings contain the same diet‐derived chemical (the alkaloid actinidine) that is present in adult defensive spray. We also explored potential causes of variation among hatchlings in the capacity to spray, using a fully crossed experiment to investigate how offspring provisioning is affected by sexual versus parthenogenetic reproduction and high versus low maternal diet. We found that high maternal diet resulted in increased egg size but slower egg development, and maternal diet interacted with genotype to affect hatchling body size. Eggs laid by male‐paired females were larger, developed more quickly, and had higher hatching success by comparison with eggs laid by unpaired females, suggesting that mating and fertilisation enhance some aspects of offspring performance. However, hatchlings produced by unpaired females had larger prothoracic glands relative to body size than did hatchlings produced by male‐paired females, suggesting that sexual reproduction is associated with reduced provisioning of offspring with defensive chemicals. Our results reveal a novel example of maternal transfer of food‐derived defence chemicals to offspring and suggest that offspring provisioning with defence chemicals is affected by female reproductive mode.